Strontium-magnesium-based anthraquinone degradation product regeneration catalyst as well as preparation method and application thereof
The strontium magnesium-based anthraquinone degradation catalyst prepared by in-situ deposition method solves the problems of low activity and short service life of the regeneration device in the prior art, and realizes efficient regeneration of anthraquinone degradation, with long service life and high catalytic activity.
Patent Information
- Application Number
- CN202411947947.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The main component of the regeneration device in the prior art is alkali-impregnated alumina, which has the disadvantages of easy loss of active components, low reactive properties and short service life, resulting in waste of resources and environmental pollution.
The strontium magnesium-based anthraquinone degradation catalyst was prepared by in-situ deposition method. The catalyst had a two-site strontium silicate/magnesium silicate, a small particle size of the active component, and was prepared by hydrothermal reaction and high-temperature calcination.
The catalyst has achieved high activity and long service life, and has high catalytic activity and selectivity for the regeneration of anthraquinone degradable substances. The regeneration amount within 72 hours reached 8.56g/L, which is far higher than the existing catalyst, and the regeneration capacity can still reach 8.12g/L after 6 months of use.
Smart Images

Figure CN119746842A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of catalyst technology, and more specifically, to a strontium magnesium-based anthraquinone degradation product regeneration catalyst and a preparation method and application thereof. Background Art
[0002] The anthraquinone method has become the main method for producing hydrogen peroxide at home and abroad by virtue of its advantages such as high degree of automation, high production efficiency and large-scale production. However, in the production process of preparing hydrogen peroxide by the anthraquinone method, due to the occurrence of side reactions in the reaction system, some degradation products will be generated, and the content of the degradation products will increase with the increase of the number of process cycles. These degradation products are usually unable to participate in the production process of cyclic production of hydrogen peroxide, and are also highly harmful. In the actual industrial production process, in order to reduce the impact of degradation products in the working fluid on hydrogen peroxide production, some degradation products are converted into effective anthraquinone by adding a regeneration device. At present, the main component of the regeneration device in the prior art is alkali-impregnated alumina, but the regeneration catalyst has the disadvantages of easy loss of active components, low regeneration activity and short service life. In addition, the regeneration catalyst needs to be frequently replaced after a period of use, which not only causes a waste of natural resources, but also generates a large amount of solid waste and pollutes the ecological environment. Therefore, it is of great significance to carry out research on new high-performance regeneration catalysts. Summary of the invention
[0003] In view of the deficiencies in the prior art, the present application provides a strontium magnesium-based anthraquinone degradation product regeneration catalyst and its preparation method and application. The present application uses an in-situ deposition method to prepare a strontium magnesium-based anthraquinone degradation product regeneration catalyst, which has the advantages of a wide range of raw material sources, a simple preparation process, green environmental protection, low production cost, and convenience for industrial production; the catalyst prepared in the present application has a strontium silicate / magnesium silicate dual site, a small particle size of the catalyst active component, high catalytic activity and selectivity for anthraquinone degradation product regeneration, and a long service life, showing great industrial application value.
[0004] In order to achieve the above objectives, in a first aspect, the present application provides a method for preparing a strontium magnesium-based anthraquinone degradation product regeneration catalyst, comprising the following steps:
[0005] Step 1: dissolving magnesium salt and surfactant in deionized water to prepare a magnesium salt solution, adding silicate solution dropwise to the magnesium salt solution to obtain a slurry, and then transferring the slurry to a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, the slurry is cooled to room temperature, and the precipitate is washed to obtain a magnesium silicate filter cake; the magnesium silicate filter cake is dispersed in deionized water to obtain a magnesium silicate slurry;
[0006] Step 2: under stirring conditions, the strontium salt solution and the silicate solution are simultaneously added dropwise to the magnesium silicate slurry. After the addition is completed, the obtained slurry is transferred to a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, it is cooled to room temperature, and the obtained precipitate is washed and dried to obtain a catalyst precursor;
[0007] Step 3: The catalyst precursor obtained in step 2 is placed in a muffle furnace for high-temperature calcination, and after the reaction is completed, it is cooled to room temperature to obtain a strontium magnesium-based anthraquinone degradation product regeneration catalyst.
[0008] Furthermore, the magnesium salt described in step 1 is any one or more combinations of magnesium chloride, magnesium nitrate or magnesium sulfate; the surfactant is any one or more combinations of glycine amino acid, dimethyl dodecylamine oxide, hexaethylene glycol monododecyl ether; and the silicate is sodium silicate or potassium silicate.
[0009] Furthermore, in step 1, the concentration of the magnesium salt solution is 1-2 mol / L, and the molar ratio of the surfactant to magnesium is 0.01-0.03:1.
[0010] Furthermore, in step 1, the concentration of silicate is 1-2 mol / L, and the Si / Mg molar ratio is 1.5-1:1.
[0011] Furthermore, the hydrothermal reaction conditions in step 1 are 160-220° C. for 5-10 h.
[0012] Furthermore, the mass content of the magnesium silicate slurry in step 1 is 2-8%.
[0013] Furthermore, the strontium salt described in step 2 is any one or more combinations of strontium carbonate, strontium nitrate, and strontium chloride, and the silicate is sodium silicate or potassium silicate.
[0014] Furthermore, in step 2, the concentration of the strontium salt solution is 0.5-1 mol / L, the concentration of the silicate solution is 0.5-1 mol / L; and the Si / Sr molar ratio is 1-1.5:1.
[0015] Furthermore, the hydrothermal reaction conditions in step 2 are 150-220° C. for 6-12 h.
[0016] Furthermore, the high temperature calcination condition in step 3 is to increase the temperature to 400-700°C at a rate of 5-10°C / min and calcine for 2-4h.
[0017] In a second aspect, the present invention provides a strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared by the above-mentioned preparation method.
[0018] In a third aspect, the present invention provides the application of the above-mentioned strontium magnesium-based anthraquinone degradation product regeneration catalyst or the preparation method of the strontium magnesium-based anthraquinone degradation product regeneration catalyst in the regeneration of anthraquinone degradation products.
[0019] The technical solution provided by this application has at least the following beneficial effects compared with the prior art:
[0020] 1) The present invention provides a method for preparing a strontium magnesium-based anthraquinone degradation product regeneration catalyst, which has the advantages of wide raw material sources, simple preparation process, no use of organic reagents, green environmental protection, low production cost, and convenience for industrial production.
[0021] 2) The catalyst prepared by the present invention has a strontium silicate / magnesium silicate dual site, the particle size of the catalyst active component is small, the catalyst has high catalytic activity and selectivity for the regeneration of anthraquinone degradation products, and has a long service life. The regeneration capacity of anthraquinone degradation products can reach 8.56 g / L within 72 hours, which is much higher than the commercial regeneration catalyst (4.23 g / L), and the regeneration capacity of the strontium magnesium-based anthraquinone degradation product regeneration catalyst of the present invention can still reach 8.12 g / L after 6 months of use. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The X-ray diffraction spectrum of the strontium magnesium-anthraquinone degradation product regeneration catalyst prepared in Example 1;
[0023] Figure 2 This is a scanning electron microscope image of the strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 1;
[0024] Figure 3 This is a graph showing the regeneration performance of the strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 1. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to understand the present application more clearly, the present application is further described in detail below in conjunction with examples and drawings. However, it should be understood that the following examples are only preferred implementation methods of the present application, and the scope of protection required by the present application shall be based on the scope defined in the claims.
[0026] In the description of the present invention, it should be noted that, if the specific conditions are not specified in the examples, the experiments were carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.
[0027] <Example>
[0028] Example 1
[0029] A strontium magnesium-based anthraquinone degradation product regeneration catalyst is prepared by the following method:
[0030] Step 1: dissolving 10.03 g (0.0640 mol) of magnesium nitrate and 0.20 g (0.0007 mol) of glycine amino acid in 150 mL of deionized water to prepare a magnesium nitrate solution, dissolving 25.02 g (0.0960 mol) of sodium silicate in 150 mL of deionized water to prepare a sodium silicate solution; using a circulating pump, adding the silicate solution dropwise to the magnesium nitrate solution at a rate of 10.6 min / mL to obtain a slurry, after the dropwise addition is completed, transferring the slurry to a hydrothermal reactor, hydrothermally reacting at 180° C. for 10 hours, cooling naturally to room temperature after the reaction is completed, and washing the precipitate with deionized water by centrifugation for 6 times to obtain a magnesium silicate filter cake; dispersing the magnesium silicate filter cake in 100 mL of deionized water to obtain a magnesium silicate slurry with a mass fraction of 6%;
[0031] Step 2: Under stirring conditions, 5 mL (0.5003 mol / L) of sodium silicate solution and 5 mL (0.5016 mol / L) of strontium nitrate solution were simultaneously added dropwise to 100 mL of magnesium silicate slurry. After the addition was completed, the obtained slurry was transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at 150° C. for 12 h. After the reaction was completed, the mixture was naturally cooled to room temperature. The obtained precipitate was washed by centrifugation with deionized water for 6 times, then transferred to a 120° C. oven for drying for 12 h, and passed through a 100-mesh sieve to obtain a catalyst precursor.
[0032] Step 3: Place the catalyst precursor obtained in step 2 in a muffle furnace, heat it to 500°C at a rate of 5-10°C / min, and calcine it for 3 hours. After the reaction is completed, cool it to room temperature to obtain a strontium magnesium-based anthraquinone degradation product regeneration catalyst.
[0033] Characterization and testing:
[0034] 1. The strontium magnesium anthraquinone degradation product regeneration catalyst obtained in Example 1 was subjected to XRD analysis, and the obtained XRD diffraction spectrum was as follows: Figure 1 As shown. Figure 1 It can be seen that the catalyst is composed of SrSiO3 and MgSiO3.
[0035] 2. The morphology of the strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 1 was characterized by scanning electron microscopy. Figure 2 As shown. Figure 2 It can be seen that the catalyst has a multi-level structure assembled by nanorods.
[0036] 3. The regeneration catalytic performance of the strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 1 was tested. The test steps were as follows: 5.00 g of strontium magnesium-based anthraquinone degradation product regeneration catalyst was added to 50 mL of working solution. After 72 hours, 50 μL of anthraquinone regeneration solution was taken and placed in a 10 mL volumetric flask and fixed to volume with anhydrous methanol. The anthraquinone regeneration amount was tested on a liquid chromatograph. The test results are as follows: Figure 3 As shown. Figure 3 It can be seen that the strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 1 has a high regeneration performance for anthraquinone degradation products, and the regeneration capacity reaches 8.56 g / L within 72 hours. After 6 months of use, the regeneration capacity can still reach 8.12 g / L.
[0037] Example 2
[0038] A strontium magnesium-based anthraquinone degradation product regeneration catalyst is prepared by the following method:
[0039] Step 1: dissolving 12.03 g (0.0760 mol) of magnesium nitrate and 0.20 g (0.0006 mol) of dimethyldodecylamine oxide in 150 mL of deionized water to prepare a magnesium nitrate solution, dissolving 26.06 g (0.1000 mol) of sodium silicate in 150 mL of deionized water to prepare a sodium silicate solution; using a circulating pump, adding the silicate solution dropwise to the magnesium nitrate solution at a rate of 10.6 min / mL to obtain a slurry, after the dropwise addition is completed, transferring the slurry to a hydrothermal reactor, hydrothermally reacting at 200° C. for 8 hours, cooling naturally to room temperature after the reaction is completed, and washing the precipitate with deionized water by centrifugation for 6 times to obtain a magnesium silicate filter cake; dispersing the magnesium silicate filter cake in 100 mL of deionized water to obtain a magnesium silicate slurry with a mass fraction of 7%;
[0040] Step 2: Under stirring conditions, 10 mL (0.5011 mol / L) of sodium silicate solution and 10 mL (0.5007 mol / L) of strontium nitrate solution were simultaneously added dropwise to 100 mL of magnesium silicate slurry. After the addition was completed, the obtained slurry was transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at 180° C. for 10 h. After the reaction was completed, the mixture was naturally cooled to room temperature. The obtained precipitate was washed by centrifugation with deionized water for 6 times, then transferred to a 120° C. oven for drying for 12 h, and passed through a 100-mesh sieve to obtain a catalyst precursor.
[0041] Step 3: Place the catalyst precursor obtained in step 2 in a muffle furnace, heat it to 400°C at a rate of 5-10°C / min, calcine it for 4 hours, and cool it to room temperature after the reaction to obtain a strontium magnesium-based anthraquinone degradation product regeneration catalyst.
[0042] test:
[0043] The regeneration catalytic performance of the strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 2 was tested, and the test steps were as follows: 5.00 g of the strontium magnesium-based anthraquinone degradation product regeneration catalyst was added to 50 mL of the working solution, and 50 μL of the anthraquinone regeneration solution was taken at 72 hours, placed in a 10 mL volumetric flask and fixed to volume with anhydrous methanol, and the anthraquinone regeneration amount was tested on a liquid chromatograph. The strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 2 has a high regeneration performance for anthraquinone degradation products, and the regeneration amount reaches 8.53 g / L within 72 hours.
[0044] Example 3
[0045] A strontium magnesium-based anthraquinone degradation product regeneration catalyst is prepared by the following method:
[0046] Step 1: dissolving 114.03 g (0.0580 mol) of magnesium nitrate and 0.20 g (0.0007 mol) of hexaethylene glycol monododecyl ether in 150 mL of deionized water to prepare a magnesium nitrate solution, dissolving 28.02 g (0.1080 mol) of sodium silicate in 150 mL of deionized water to prepare a sodium silicate solution; using a circulating pump, adding the silicate solution dropwise to the magnesium nitrate solution at a rate of 10.6 min / mL to obtain a slurry, after the dropwise addition is completed, transferring the slurry to a hydrothermal reactor, performing a hydrothermal reaction at 220° C. for 6 h, cooling naturally to room temperature after the reaction is completed, and washing the precipitate with deionized water by centrifugation for 6 times to obtain a magnesium silicate filter cake; dispersing the magnesium silicate filter cake in 100 mL of deionized water to obtain a magnesium silicate slurry with a mass fraction of 8%;
[0047] Step 2: Under stirring conditions, 15 mL (0.5001 mol / L) of sodium silicate solution and 15 mL (0.5014 mol / L) of strontium nitrate solution were simultaneously added dropwise to 100 mL of magnesium silicate slurry. After the addition was completed, the obtained slurry was transferred to a hydrothermal reactor and subjected to a hydrothermal reaction at 200°C for 8 h. After the reaction was completed, the precipitate was naturally cooled to room temperature, and the obtained precipitate was washed by centrifugation with deionized water for 6 times, then transferred to a 120°C oven for drying for 12 h, and passed through a 100-mesh sieve to obtain a catalyst precursor;
[0048] Step 3: Place the catalyst precursor obtained in step 2 in a muffle furnace, heat it to 600°C at a rate of 5-10°C / min, calcine it for 2h, and cool it to room temperature after the reaction to obtain a strontium magnesium-based anthraquinone degradation product regeneration catalyst.
[0049] test:
[0050] The regeneration catalytic performance of the strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 3 was tested, and the test steps were as follows: 5.00 g of the strontium magnesium-based anthraquinone degradation product regeneration catalyst was added to 50 mL of the working solution, and 50 μL of the anthraquinone regeneration solution was taken at 72 hours, placed in a 10 mL volumetric flask and fixed to volume with anhydrous methanol, and the anthraquinone regeneration amount was tested on a liquid chromatograph. The strontium magnesium-based anthraquinone degradation product regeneration catalyst prepared in Example 3 has a high regeneration performance for anthraquinone degradation products, and the regeneration amount reaches 8.49 g / L within 72 hours.
[0051] Comparative Example 1
[0052] The catalytic performance of a commercially available alumina-supported sodium hydroxide regeneration catalyst was tested, and the test steps were as follows: 5.00 g of a commercially available alumina-supported sodium hydroxide regeneration catalyst was added to 50 mL of working solution, 50 μL of anthraquinone regeneration solution was taken after 72 hours, placed in a 10 mL volumetric flask and made up to volume with anhydrous methanol, and the anthraquinone regeneration amount was tested on a liquid chromatography. The regeneration amount within 72 hours was 4.23 g / L, and the regeneration performance dropped to 2.36 g / L after 3 months of use.
Claims
1. A method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst, characterized in that: The following steps are involved: Step 1: dissolving a magnesium salt and a surfactant in deionized water to prepare a magnesium salt solution, adding a silicate solution dropwise to the magnesium salt solution to obtain a slurry, and then transferring the slurry to a hydrothermal reactor for a hydrothermal reaction. After the reaction is completed, the slurry is cooled to room temperature, and the precipitate is washed to obtain a magnesium silicate filter cake, and the magnesium silicate filter cake is dispersed in deionized water to obtain a magnesium silicate slurry; Step 2: under stirring conditions, the strontium salt solution and the silicate solution are simultaneously added dropwise to the magnesium silicate slurry. After the addition is completed, the obtained slurry is transferred to a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, it is cooled to room temperature, and the obtained precipitate is washed and dried to obtain a catalyst precursor; Step 3: The catalyst precursor obtained in step 2 is placed in a muffle furnace for high-temperature calcination, and after the reaction is completed, it is cooled to room temperature to obtain a strontium magnesium-based anthraquinone degradation product regeneration catalyst.
2. The method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst according to claim 1, characterized in that: The magnesium salt described in step 1 is any one or more combinations of magnesium chloride, magnesium nitrate or magnesium sulfate; the surfactant is any one or more combinations of glycine amino acid, dimethyl dodecylamine oxide, hexaethylene glycol monododecyl ether; the silicate is sodium silicate or potassium silicate.
3. The method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst according to claim 1, characterized in that: The concentration of the magnesium salt solution in step 1 is 1-2 mol / L, and the molar ratio of the surfactant to magnesium is 0.01-0.03:
1.
4. The method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst according to claim 1, characterized in that: In step 1, the concentration of silicate is 1-2 mol / L, and the Si / Mg molar ratio is 1.5-1:
1.
5. The method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst according to claim 1, characterized in that: The conditions of the hydrothermal reaction in step 1 are 160-220° C. for 5-10 h.
6. The method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst according to claim 1, characterized in that: The mass content of the magnesium silicate slurry in step 1 is 2-8%.
7. The method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst according to claim 1, characterized in that: The strontium salt described in step 2 is any one or more combinations of strontium carbonate, strontium nitrate, and strontium chloride, and the concentration of the strontium salt solution is 0.5-1 mol / L; the silicate is sodium silicate or potassium silicate, and the concentration of the silicate solution is 0.5-1 mol / L; the Si / Sr molar ratio is 1-1.5:
1.
8. The method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst according to claim 1, characterized in that: The high temperature calcination conditions in step 3 are to increase the temperature to 400-700°C at a rate of 5-10°C / min and calcine for 2-4h.
9. A method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst, characterized in that: The catalyst is prepared by the method for preparing a strontium magnesium anthraquinone degradation product regeneration catalyst as described in any one of claims 1 to 8.
10. Use of the method for preparing a strontium magnesium-based anthraquinone degradation product regeneration catalyst according to any one of claims 1 to 8 or the method for preparing a strontium magnesium-based anthraquinone degradation product regeneration catalyst according to claim 9 in the regeneration of anthraquinone degradation products.
Citation Information
Patent Citations
Process for producing propylene oxide
CN102459213A
Palladium-alumina-cordierite composite material, and preparation method and application thereof
CN108940270A
Method for detecting anthraquinone and anthrone substances in water
CN111272908A
Iron-molybdenum catalyst for preparing formaldehyde through methanol oxidation and preparation method of iron-molybdenum catalyst
CN115845865A
Preparation method of attapulgite-based magnesium silicate anthraquinone regenerated catalyst, anthraquinone regenerated catalyst and application thereof
CN117602636A